Evaluation Of Tacrolimus, Associated Adverse Effects, Quality Of Life, And Treatment Satisfaction Among Kidney Transplant Patients In Riyadh, Saudi Arabia - Ahmed Alboghdadly, Amany Mohamed Hussien (2023)
The number of renal transplanted patients in Saudi Arabia is markedly increased. Tacrolimus is a well-known immunosuppressive drug used to prevent allograft rejection. Due to tacrolimus- unwanted adverse effects, narrow therapeutic index, drug-drug interactions, and significant inter-individual variability in pharmacokinetics, it requires constant therapeutic drug monitoring. This study aims to determine the tacrolimus-associated adverse effects and the factors associated with their occurrence, acute cellular rejection, and graft loss. Also, to evaluate the relationship between tacrolimus trough concentration (FK506-C0) levels with all of these variables. Finally, the effect of demographic, clinical, and social factors on health-related quality of life (HRQoL) and treatment satisfaction in tacrolimus-treated patients’ post-renal transplantation (RTP) in Saudi population was investigated. It is a pre-experimental study design conducted at the Security Forces Hospital in Riyadh, Saudi Arabia. The study included all patients over the age of 18 who received a kidney transplant between January 2006 and January 2019 and were treated with tacrolimus, mycophenolate mofetil, and prednisolone (322 patients). Patients were monitored at each clinic visit and followed up until September 2019